ARTIKEL METAFORA ANTROPOMORFIS SEBAGAI LAMBANG IDENTITAS KULTURAL MASYARAKAT SABU - Frans Bustan Agustinus Mahur (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2019)
This research investigates the relationship between Sabu language, Sabu culture, and conceptualization of Sabu people, as reflected in the anthropomorphic metaphor as the cultural identity of the Sabu in terms of their form and meaning. This study is illustrated from cultural linguistics, a new theoretical perspective in cognitive linguistics that explores the relationship of language, culture, and conceptualization. This research is descriptive. The results show that there is a close relationship between Sabu language, Sabu culture, and conceptualization of Sabu people, as reflected in the anthropomorphic metaphor shown by the use of human organs attached to entities in the physical environment. In addition to creating new forms, attachments also present new meanings because of the expansion of meanings from denotative to connotative meanings. Verbal expressions in Sabu that show anthropomorphic metaphorical characteristics as cultural identities of Sabu people, among other things, wat'tu ai 'spring' which refers to the spring and kepue lede 'foot of the mountain' which refers to the bottom of the mountain. Because language functions as the cultural identity of its people, it is recommended that Sabu language must be maintained.